Relationship between motor proficiency and body composition in 6- to 10-year-old children - Marmeleira, José (2018)
Aim: The aim of this study is to examine the relationship between motor skill competence and body composition of 6- to 10-year-old children. Methods: Seventy girls and 86 boys participated. Body composition was measured by body mass index and skinfold thickness. Motor proficiency was evaluated through the Bruininks-Oseretsky Test of Motor Proficiency-Short Form, which included measures of gross motor skills and fine motor skills. Results: Significant associations were found for both sexes between the percentage of body fat and (i) the performance in each gross motor task, (ii) the composite score for gross motor skills and (iii) the motor proficiency score. The percentage of body fat was not significantly associated with the majority of the fine motor skills items and with the respective composite score. Considering body weigh categories, children with normal weight had significantly higher scores than their peers with overweight or with obesity in gross motor skills and in overall motor proficiency. Conclusions: Children’s motor proficiency is negatively associated with body fat, and normal weight children show better motor competence than those who are overweight or obese. The negative impact of excessive body weight is stronger for gross motor skills that involve dynamic body movements than for stationary object control skills; fine motor skills appear to be relatively independent of the constraints imposed by excessive body weight.